The Erosion of Privacy in the Digital Age: A Constitutional Challenge in Indonesia - Syahwami, Syahwami; Hamirul, Hamirul (Enigma Institute, 2024)
The digital age has revolutionized communication and information access, but it has also brought significant challenges to the fundamental right to privacy. In Indonesia, the legal framework struggles to keep pace with technological advancements, raising concerns about the erosion of privacy protections. This study examines the constitutional challenges and practical implications of digital privacy erosion in Indonesia. This study employs a mixed-methods approach. First, a comprehensive review of Indonesian constitutional law, privacy legislation, and relevant court decisions is conducted. Second, observational data is collected through a survey of Indonesian internet users (n = 500) to assess their privacy awareness, experiences with data breaches, and perceptions of legal protections. Data analysis involves both qualitative legal interpretation and quantitative statistical analysis. The study reveals a significant gap between constitutional guarantees of privacy and the reality of data collection and surveillance practices in Indonesia. Observational data highlights widespread concerns among Indonesian internet users about privacy violations, with a majority experiencing data breaches and feeling inadequately protected by existing laws. Legal analysis indicates that existing legislation is often vague, outdated, and fails to address the unique challenges posed by digital technologies. In conclusion, this study underscores the urgent need for comprehensive legal reforms in Indonesia to protect digital privacy. Constitutional challenges must be addressed through clear and enforceable legislation that aligns with international standards. Additionally, public awareness campaigns and educational initiatives are crucial to empower individuals to protect their personal information in the digital age.